Pola Literasi Informasi Pemustaka di Perpustakaan Politeknik Negeri Padang - Fitaloka, Yollanda; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This study aims to describe: (1) a step in obtaining literacy skill information in the library of State Polytechnic Padang; (2) how to use information in the skill of literacy pattern in Library of State Polytechnic of Padang. Based on analyzing the data, the following conclusions are summarized. First, there are some steps in obtaining literacy skill information in Library of State Polytechnic of Padang that is to formulate information requirement is the first step in conducting information searching, librarian will know what information is used for what. Allocate and evaluate the quality of information that can be seen from the use of such information and the credibility of the information to be a lesson for themselves. Saving and rediscovering information, a librarian must be able to store the information which is already obtained and already in the fulfillment of information needs and the inclusion of resources is also done to appreciate the scientific work as well as for easy rediscovery. Secondly, there is a different way of using information in skill of literacy pattern in Library of State Polytechnic of Padang with skill of contracting relevant information. Respondents have been able to estimate relevant information or have been able to combine information. In contracting, the user first evaluates the information by looking at who wrote the information and the source used by the user.Keyword: literacy pattern, information